Desarrollo de la lectoescritura en el proceso de enseñanza aprendizaje de los alumnos del tercer año de la Unidad Educativa Belisario Quevedo en el período lectivo 2018-1019. - Rengifo Rivera, Teresa del Carmen (2020)
The main objective of this research is to demonstrate the teaching-learning process through the development of Literacy of the students of the third year of the Belisario Quevedo Educational Unit in Latacunga, Cotopaxi province, the methodology that was used was with a qualitative approach since Its objective was to test the theories found in the place where this research was applied, the bibliographic research taken from several works was used, whose approach is positivist, since it describes the need that children have to improve the development of Literacy in the process teaching-learning through a proposal focused on a specific objective; It began with the perceptual level because it allowed us to explore and describe everything that is defined about the development of Literacy in the teaching-learning process, it was also apprehensive since it allowed us to compare and analyze the results obtained in this research, the method was applied deductive because it started from the observation of the problem, that is, the development of Literacy, finally the proposal was applied as an alternative solution to the development of Literacy, as a conclusion there was evidence of a great strengthening in the process of literacy through the ludic techniques, the students also developed new strengths with the application of these new processes and it was found that ludic techniques improve and broaden the degree of attention of the students, which, if not attended immediately, would directly harm the learning and development of literacy.